Proteomic Analysis Reveals a Novel Therapeutic Strategy Using Fludarabine for Steroid-Resistant Asthma Exacerbation - Liu, Xiaoming; Li, Xiang; Chen, Ling; Hsu, Alan Chen-Yu; Asquith, Kelly L.; Liu, Chi; Laurie, Karen; Barr, Ian; Foster, Paul S.; Yang, Ming (Frontiers in Immunology, 2022)
Virus-induced asthma exacerbation is a health burden worldwide and lacks effective treatment. To better understand the disease pathogenesis and find novel therapeutic targets, we established a mouse model of steroid (dexamethasone (DEX)) resistant asthma exacerbation using ovalbumin (OVA) and influenza virus (FLU) infection. Using liquid chromatography-tandem mass spectrometry (LC-MC/MS), we performed a shotgun proteomics assay coupled with label-free quantification to define all dysregulated proteins in the lung proteome of asthmatic mice. Compared to control, 71, 89, and 30 proteins were found significantly upregulated by at least two-fold (p-value ≤ 0.05) in OVA-, OVA/FLU-, and OVA/FLU/DEX-treated mice, respectively. We then applied a Z-score transformed hierarchical clustering analysis and Ingenuity Pathway Analysis (IPA) to highlight the key inflammation pathways underlying the disease. Within all these upregulated proteins, 64 proteins were uniquely highly expressed in OVA/FLU mice compared to OVA mice; and 11 proteins were DEX-refractory. IPA revealed two of the most enriched pathways associated with these over-expressed protein clusters were those associated with MHC class I (MHC-I) antigen-presentation and interferon (IFN) signaling. Within these pathways, signal-transducer-and-activator-of-transcription-1 (STAT1) protein was identified as a key regulator of inflammation, contributing to the pathogenesis of exacerbation and the underlying steroid resistance based on the label-free quantification; and this was further confirmed by both Parallel Reaction Monitoring (PRM) proteomics assay and western blots. Further pharmacological inhibition of STAT1 by Fludarabine restored the responsiveness of OVA/FLU mice to DEX and markedly suppressed disease severity. Taken together, this study describes the proteomic profile underpinning molecular mechanisms of FLU-induced asthma exacerbation and identifies STAT1 as a potential therapeutic target, more importantly, we provided a novel therapeutic strategy that may be clinically translated into practice.